Effect of Cu doping on the electrical Properties of ZnTe by Vacuum Thermal Evaporation - M. Ali, Sarmad M.; Shehab, Alia A.A.; Maki, Samir A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
In this study, the ZnTe thin films were deposited on a glass substrate at a thickness of 400nm using vacuum evaporation technique (2×10-5mbar) at RT. Electrical conductivity and Hall effect measurements have been investigated as a function of variation of the doping ratios (3,5,7%) of the Cu element on the thin ZnTe films. The temperature range of (25-200°C) is to record the electrical conductivity values. The results of the films have two types of transport mechanisms of free carriers with two values of activation energy (Ea1, Ea2), expect 3% Cu. The activation energy (Ea1) increased from 29meV to 157meV before and after doping (Cu at 5%) respectively. The results of Hall effect measurements of ZnTe , ZnTe:Cu films show that all films were (p-type), the carrier concentration (1.1×1020 m-3) , Hall mobility (0.464m2/V.s) for pure ZnTe film, increases the carrier concentration (6.3×1021m-3) Hall mobility (2m2/V.s) for doping (Cu at 3%) film, but decreases by increasing Cu concentration.